A data-driven approach to enhance urban infrastructure for sustainable mobility and improved quality of life in highly populated cities. Case study: Barcelona - Sanchez-Sepulveda, Monica V.; Navarro, Joan; Amo-Filva, Daniel; Fonseca, David; Antúnez-Anea, Felipe; Barranco-Albalat, Albert (Frontiers in Built Environment, 2024)
The concentration of populations in large cities has resulted in significant challenges affecting residents’ quality of life, particularly mobility and environmental pollution. Addressing these issues is crucial for enhancing environmental, social, and economic wellbeing. This study proposes leveraging Open Data repositories to identify critical points in urban infrastructure for promoting accessible, sustainable, and healthy mobility. We hypothesize that by analyzing and optimizing urban infrastructure based on available data, it is possible to mitigate the negative impacts of urbanization on mobility and environmental quality. A data-driven tool, incorporating data visualization, exploratory analyses, and classification and clustering algorithms, was employed to develop a system that not only presents data intuitively but also offers insights and recommendations for improvement. The findings, based on a case study in Barcelona, are transferable to other cities worldwide, offering valuable insights for urban planning professionals in future city improvement projects. While the city of Barcelona serves as a case study, the methodology is transferable to other cities worldwide.